ADAPTASI HUKUM PERIKATAN DAN HUKUM DAGANG INDONESIA TERHADAP TRANSAKSI EKONOMI DIGITAL: KAJIAN NORMATIF ATAS KETIDAKMEMADAIAN KODIFIKASI - Firdany, Irza Ahmad (Jurnal HUKUM BISNIS, 2026)
This study examines the normative inadequacy of Indonesian contract law (Book III of the Civil Code) and commercial law (KUHD) in addressing the realities of digital economy transactions. Both codifications are products of Dutch legal transplantation designed for a 19th-century economy; the academically relevant question is not whether they are adequate, they clearly are not, but at which points the inadequacy is most severe and what needs to be done. Normative legal research methodology is employed with statutory, conceptual, and comparative approaches. Five normative gaps are identified and analyzed in depth: (1) legal uncertainty regarding the moment and place of electronic contract formation; (2) absence of a clear platform liability regime; (3) inconsistency between rules of evidence in the Civil Code and the ITE Law; (4) the KUHD's inability to qualify digital financial instruments; and (5) a legal vacuum in small-claim digital dispute resolution. The study argues that the adaptive interpretation approach that has been relied upon has structural limits that cannot be overcome without systemic legislative renewal. Keywords: Contract Law, Commercial Law, Electronic Contract, Digital Platform, Codification Reform